Toxic epidermal necrolysis induced by moxifloxacin and exacerbated by clindamycin in an elderly patient: A case report - Wang, Yongguang; Guo, Qizheng; Li, Zhenyang; Gan, Guifen; Pan, Chun (Frontiers in Medicine, 2025)
Toxic Epidermal Necrolysis (TEN) is a severe skin-mucosal reaction induced by medications, commonly characterized by blister formation and widespread epidermal detachment. Typical causative agents include allopurinol, antibiotics, anticonvulsants, and non-steroidal anti-inflammatory drugs (NSAIDs), with trimethoprim/sulfamethoxazole and penicillin being the most frequently implicated among antibiotics. However, lincosamide antibiotics as the cause of aggravation are rarely reported in clinical settings. This case report presents a patient with TEN induced by quinolone antibiotics, who experienced rapid progression of the condition after combining with lincomycin antibiotics. Clinical remission was achieved through a combination of corticosteroids, intravenous immunoglobulin, and plasma exchange therapy. This report aims to enhance clinicians’ understanding of TEN by providing a detailed case presentation and discussion.